The Impact of Decentralization on Public Service Provision - Carolina da Cruz; Marito Magno; Felicidade Xavier (Eduvest - Journal of Universal Studies, 2026)
This study aimed to determine and explain the impact of decentralization on improving the quality of public services, particularly in terms of accessibility, responsiveness, and transparency. It also aimed to compare the impact of decentralization in Timor-Leste with that of other countries implementing decentralization in public service provision. This research employed a normative juridical approach. Data were collected through a literature review involving primary legal materials, secondary legal materials, and relevant non-legal materials. The data were analyzed using descriptive-analytical legal research methods. The findings indicate that decentralization in Timor-Leste, by granting greater authority to local governments, has the potential to improve public service quality in several aspects, including accessibility, responsiveness, and transparency. By understanding local needs more effectively, local governments are expected to deliver more appropriate and efficient services. However, the success of decentralization in improving public services is also influenced by various factors, including resource availability, institutional capacity, the competence of public officials, and the effectiveness of oversight mechanisms. A comparison between Timor-Leste and Vietnam shows that, although both countries have implemented decentralization in public service provision, their outcomes differ due to distinct political, historical, and institutional contexts. Timor-Leste, with its post-independence state-building experience, faces challenges in implementing decentralization due to limited resources and relatively developing institutional capacity. In contrast, Vietnam has implemented decentralization within the framework of a centralized one-party political system, which influences the implementation of regional autonomy and its implications for public service delivery.